RANCANG BANGUN ALAT PERONTOK LADA DENGAN PENGGERAK ENGKOL UNTUK PENGOLAHAN LADA HITAM - RISFAHERI RISFAHERI; TATANG HIDAYAT (Pusat Penelitian dan Pengembangan Perkebunan, 1999)
Design of the hand-powered thresher for black pepper processingProcessing of pepper berries (Piper nigrum L.) into black pepper needs thresing to remove the beries from the stalks prior to sundrying. Until now, the threshing practice is caried out by traditional method in which the pepper beries are trampled. This method is not eficient nor hygienic and it also causes high losses of the berries. To overcome those problems, a hand-powered thesher has been designed. The experiment consisted of thee steps, namely designing, constructing and testing. The threshing mechanism was based on impact and friction, whereas the separation of the berries from the stalks was based on the difference in shape and dimension. The dimension of the pepper thesher is 900 mm length, 450 mm width, and I 200 mm height. The test results showed that the hand-powered thresher have a good performance. The capacity of the thesher is 100 kg of pepper berries (berries + stalks) per hour. The operational cost is Rp 30.02 per kg of pepper beries, cheaper than that of the traditional theshing method (Rp 50/kg). This equipment is easy to apply in rural area, and can covee the theshing operation of 2.1 hectare of pepper plantation during harvesting periode.